Pánico escénico: estrategias de combinación psicológicas y performativas para su superación. (2020)
Within the academic spaces in the training of future professionals in music the skills they are acquiring must be constantly tested. Many times these tests are carried out in scenarios that can become contexts in which stage panic appears; this panic understood as an expression characterized by high levels of anxiety as a consequence of exposing oneself to situations that can be threatening or uncomfortable (Itziar Iruarrizaga, 1999). For him particular case, the fact of making presentations in front of experts who issue concepts, or the general public that watches the performances, make it possible for musicians to be in a constant evaluation situation, since those who observe have the ability to express opinions or concepts against what they are seeing and thus judge the technical and professional capabilities of musicians.